Analisis Pengaruh CAR, LDR, DER, BI Rate dan Inflasi Terhadap ROA Pada 10 Bank Besar Yang Ada di Bursa Efek Indonesia - Sandra Kurniawati; Zilal Hamzah; Tri Kunawangsih (Lembaga Penelitian Universitas Trisakti, 2018)
In carrying out operations of each company are always directed at achieving the goals set. The main objective of the company is to maximize wealth for its shareholders or for the owner of the company (stakeholders). One way to achieve the company’s goal is to increase the profitability of the company. Profitability or earnings capability is very important for the company because it can reflect the success and survival of a company. The profitability of the company demonstrating excellence in business competition. The higher the level of profitability of the company’s performance is getting better. This study attempts to examine the effect of capital, liquidity, solvency, concentration ratio, inflation, BI rate, toward to profitability. The analysis technique used is panel regression with least squares equation with significance level of 10%. The results show that capital has positive but not significant influence, liquidity has positive but not significant influence, solvency have significant effect and negative, inflation have positive but not significant influence, and BI rate have significant and negative influence toward profitability.